ANALISIS PENGARUH KOMPENSASI RUGI FISKAL, CORPORATE GOVERNANCE, RETURN ON ASSET, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013–2017 - Ongkopranoto, Martha Nandana; Madyakusumawati, Synthia; Tarigan, Thia Margareta (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2020)
This study aims to determine the effect of fiscal loss compensation, corporate governance, return on assets, leverage, and firm size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. Analysis of the data used is descriptive statistical analysis, classical assumption test, and hypothesis testing using the SPSS. The study using secondary data in the form of financial statements of manufacturing sector companies listed on the Indonesia Stock Exchange and audited during 2013-2017. Based on the results of regression testing, it is known that the fiscal loss compensation variable has a negative effect, and return on assets has a positive effect on tax avoidance, while corporate governance, leverage, and firm size do not affect tax avoidance.